2015
DOI: 10.1155/2015/707168
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics of Rotation in Joints of the Lower Limbs and Pelvis during Gait: Early Results—SB ACLR Approach versus DB ACLR Approach

Abstract: It is difficult to find publications comparing rotation kinematics in large joints of the lower limbs and pelvis during gait in patients after single-bundle (SB) reconstruction of the anterior cruciate ligament (ACLR) with double-bundle (DB) ACLR of the knee. The aim of this study was to compare rotation kinematics in ankle, knee, and hip joints and the pelvis during gait in the 14th week after SB and DB ACLR. The subjects were males after SB (n = 10) and DB (n = 13) ACLR and a control group (n = 15). The valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 41 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…The positional data has been used to perform biomechanical analysis in static and dynamic conditions. [1][2][3]25 However, marked motion capture systems have some limitations. They are expensive and few clinical centers can afford them.…”
Section: Discussionmentioning
confidence: 99%
“…The positional data has been used to perform biomechanical analysis in static and dynamic conditions. [1][2][3]25 However, marked motion capture systems have some limitations. They are expensive and few clinical centers can afford them.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25][26] This was also confirmed in our research. [27][28][29] Despite the existence of the LARS technique since the 1990s, it is a rarely performed procedure compared to natural transplants. There are also few long-term postoperative follow-ups.…”
Section: Discussionmentioning
confidence: 99%
“…Results from (Ferrari et al 2008) also demonstrate four out of five protocols estimating knee external rotation in swing, with only one protocol measuring internal rotation. Further, (Czamara et al 2015) measured four degrees of knee external rotation at the point of maximal knee flexion in swing. This supports the results from (Ferrari et al 2008) and the results from the SCM model in the current study which demonstrated external rotation in swing.…”
Section: Discussionmentioning
confidence: 99%